Effect of PCL nanofiber mats coated with chitosan microcapsules containing cinnamon essential oil for wound healing - Mahmoud Osanloo; Fariba Noori; Alireza Tavassoli; Mohammad Reza Ataollahi; Ali Davoodi; Morteza Seifalah-Zade; Ali Taghinezhad; Narges Fereydouni; Arash Goodarzi (BMC, 2023)
Abstract Introduction Cinnamon is one of the most common spices that has been studied for its anti-inflammatory, antioxidant, and antibacterial properties in wound healing. The purpose of this study was to evaluate the effectiveness of polycaprolactone nanofiber mats coated with chitosan microcapsules loaded with cinnamon essential oil in wound healing. Material and methods For this purpose, chitosan microcapsules containing cinnamon essential oil (µCS-CiZ) were prepared by ion gelation and PCL nanofibers by electrospinning. The size of the µCS-CiZ and the morphology of nanofibers were evaluated by DLS and FESEM methods. In order to evaluate wound healing, 48 rats in 4 groups of Control, µCS-CiZ, PCL, and PCL + µCS-CiZ and were examined on days 7, 14, and 21 in terms of macroscopy (wound closure rate) and histology (edema, inflammation, vascularity, fibrotic tissue, and re-epithelialization). Results The particle size of the µCS-CiZ and the diameter of the nanofibers were estimated at about 6.33 ± 1.27 μm and 228 ± 33 nm, respectively. On day 21, both µCS-CiZ and PCL groups showed a significant decrease in wound size compared to the control group (P < 0.001). The PCL + µCS-CiZ group also showed a significant decrease compared to the µCS-CiZ (P < 0.05) and PCL groups (P < 0.05). Histological results showed further reduction of edema, inflammation, and vascularity in granulation tissue and appearance of moderate to marked fibrotic tissue in PCL + µCS-CiZ group compared with the other groups. Conclusion The results of the study showed that the combined use of PCL + µCS-CiZ indicates a synergistic effect on improving wound healing.